Analysis of the pharmacodynamic difference between Xiaojin Pills taken with Chinese Baijiu and water based on serum pharmacochemistry and pharmacokinetics. (10th January 2023) - Song, Jiao; Liao, Wei; Deng, Xuan; Zhang, Dingkun; Lin, Junzhi; Xu, Runchun; Han, Li
Abstract: Ethnopharmacological relevance: Xiaojin Pills (XJPs), which has the function of dissipating knots and dispersing swelling, removing blood stasis, and relieving pain, is a classic prescription for the treatment of mammary glands hyperplasia. It is also the first choice of Chinese patent medicine for the clinical treatment of mammary glands hyperplasia in contemporary traditional Chinese medicine clinics. Previous studies have shown that the efficacy of XJPs "taken orally after soaked with Chinese Baijiu" in tradition was significantly better than that of taking it orally with water in modern in terms of activating the blood, anti-inflammation, analgesia, anti-mammary gland hyperplasia, anti-breast cancer and its metastasis in vitro and in vivo, especially under low-dose conditions. However, the material basis for the difference in efficacy between XJP&B and XJP&W is still unclear. Aim of the study: To analyze the material basis of the significant difference in efficacy between XJP&B and XJP&W from the perspective of serum pharmacochemistry and pharmacokinetics, and clarified the scientific connotation of XJPs "taken orally after soaked with Chinese Baijiu". Materials and methods: Ultra-high performance liquid chromatography-mass spectrometry combined with a multivariate statistical analysis method were used to screen the differential components in the Chinese Baijiu extract and the water extract of XJPs and the corresponding residues, so as to clarify the differential components between XJP&B and XJP&W in vitro . The migrating components in the blood after XJP&B and XJP&W were characterized by serum pharmacochemical methods, in order to clarify the differential components in rats. The pharmacokinetic parameters of the representative components absorbed into the blood were compared between XJP&B and XJP&W by the pharmacokinetics study method, in order to determine the dynamic changes of the representative components in rats. Results: The identification results of different components in vitro showed that there were 34 and 12 different compounds between the Chinese Baijiu extract and water extract of XJPs, and the residues after Chinese Baijiu extraction and water extraction, respectively. The content of different components such as arachidonic acid, ursolic acid, 3-acetyl-11-keto-β-boswellic acid, 2α-hydroxyursolic acid, and oleanolic acid was higher in the Chinese Baijiu extract, which was more than twice the content in the water extract. The results of the serum pharmacochemistry study indicated that 42 prototype components were identified in the serum of rats after XJP&B and XJP&W, including organic acids, alkaloids, steroids, and terpenoids. And XJP&B increased the absorption of the prototype components of organic acids in XJPs into the blood. The pharmacokinetic study results of representative components demonstrated that the mean plasma concentration-time profile and pharmacokinetic parameters of muscone, aconitine, and 3-acetyl-11-keto-β-boswellic acid were significantly different between XJP&B and XJP&W. Compared with XJP&W, the Cmax and AUC0-t of muscone and aconitine in XJP&B were higher, and the T1/2 and MRT0-t of 3-acetyl-11-keto-β-boswellic acid in XJP&B were relatively longer. Conclusion: This research proved that "taking XJPs orally after being soaked with Chinese Baijiu" can increase the dissolution and absorption of active ingredients in XJPs, increase the plasma concentration and content of representative ingredients, and prolong its action time, thus enhancing the biological activity of XJPs in vitro and in vivo . To a certain extent, this study revealed the material basis of the significantly better efficacy of XJP&B than XJP&W and clarified the scientific connotation of XJPs "taken orally after soaked with Chinese Baijiu", which can provide a theoretical basis for the optimization of XJPs' clinical administration method. Graphical abstract: Image 1 Highlights: XJP&B can increase the dissolution of blood-activating and anti-tumor active ingredients of Xiaojin Pills. XJP&B can increase the absorption of the active ingredient organic acids of Xiaojin Pills into the blood. XJP&B can increase the blood concentration and content of muscone, aconitine, and 3-acetyl-11-keto-β-boswellic acid in rats. To some extent, this research revealed the material basis for the significantly better efficacy of XJP&B than that of XJP&W.